Implementation of Green Banking Policy at Indonesian Islamic Banks - Arsy, Rastiana Alfaaghiyatul; Agriyanto, Ratno; Fuadi, Nasrul Fahmi Zaki (Institut Agama Islam (IAI) SEBI, 2023)
Therefore, this study aims to determine the effect of knowledge and policies on the implementation of green banking at Bank Syariah Indonesia (BSI) Branch Offices (KC) Semarang. This research uses a quantitative research type with purposive sampling using a census technique. Researchers distributed a questionnaire (questionnaire) to collect data. This research method is a quantitative method. This research utilizes quantitative methods as a method for analyzing research questions. This study obtains primary data by interacting directly in the field and the results of distributing questionnaires to samples that will be distributed to respondents from Bank BSI employees. This questionnaire tool can be estimated using a Likert scale. Regression analysis method is a method of statistical science that shows the relationship or causal relationship between two or more variables. To prove the hypothesis in this study, researchers used statistical tests supported by econometric tests using the Simultaneous Test (F Test), Partial Test (T Test), and Coefficient of Determination Test (R²). The results showed that knowledge have no significant effect on the application of green banking. This is indicated by the t value of 0.973 with a significance value of 0.334. Meanwhile, the policy has a positive and significant effect on the implementation of green banking.